ROLE OF PEDAGOGICAL TECHNOLOGIES IN EDUCATION IN UZBEKISTAN (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
This article briefly discusses the methods of forming the interest of schoolchildren in technology during extracurricular activities.